Relationship between Vitamin D Receptor Gene Polymorphisms and Migraine without Aura in an Iranian Population. (25th July 2013) - Motaghi, Mohammad; Haghjooy Javanmard, Shaghayegh; Haghdoost, Faraidoon; Tajadini, Mohamadhasan; Saadatnia, Mohammad; Rafiee, Laleh; Zandifar, Alireza
Abstract : Background . Inflammation has a key role in migraine pathophysiology. Vitamin D is an effective anti-inflammatory agent. The aim of this study was to investigate the association between migraine and two vitamin D receptor (VDR) polymorphisms (TaqI and FokI) and also the relationship between VDR polymorphisms and headache severity. Methods . In this case-control study we assessed 103 patients with newly diagnosed migraine without aura and 100 healthy subjects. Patients filled headache impact test-6 (HIT-6) as a tool to assess headache severity. Results . Genotype frequencies of VDR were significantly different between control and migraine patients. Heterozygote genotypes (Ff and Tt) were statistically more frequent in the migraine patients than the control subjects both for TaqI gene (P = 0.018 ; OR = 1.81, 95% CI = 1.03–3.18) and FokI gene polymorphisms (P = 0.001 ; OR = 2.91, 95% CI = 1.47–5.77). Also f and t alleles were more frequent in the migraine patients. Total HIT-6 score was significantly different between FokI heterozygote and homozygote patients (60.32 ± 1.87 versus 49.87 ± 2.69, resp., P = 0.004 ). Conclusions . In conclusion our results showed that TaqI and FokI gene polymorphisms are associated with migraine without aura in Iranians patients. Also headache severity in FokI heterozygote patients was significantly greater than in the homozygote patients.